Phosphorus and Selenium Interaction Effects on Agronomic Biofortification of Cowpea Plants - Santos, Elcio Ferreira; Figueiredo, Caroline Oliveira; Rocha, Mateus Andrey Pires; Lanza, Maria Gabriela Dantas Bereta [UNESP]; Silva, Vinícius Martins [UNESP]; Reis, André Rodrigues [UNESP] (Springer Nature, 2023)
Selenium (Se) as selenite and phosphorus (P) have similarities in uptake and assimilation by plants. Selenium content in cowpea grains might be affected by P, which could affect Se and P concentration in other plant tissues and the biosynthesis of sugars and chlorophyll. This study investigated the effects of Se and P interaction on cowpea plants grown under pot conditions. The experiment involved two cultivars, BRS Xiquexique and BRS Tumucumaque, and a 5 × 2 interaction between five rates of Se (0, 5, 10, 20, and 40 g ha−1) and two rates of P (low and adequate P). The results showed that adequate P supply led to the highest dry mass production and Se concentration in shoots, roots, and grains, starting at the rate of 5 g ha−1 of Se. The Se rates also had an effect on chlorophyll and carotenoids concentrations, and the combined application of Se and P increased the total sugar concentration in the grain. However, low P supply decreased Se accumulation in cowpea seeds. The study highlighted that the interaction between Se and P affected cowpea yield and growth, and an adequate supply of P in the soil increased Se accumulation in cowpea grains. The study also suggested that lower doses of Se increased sugar and pigment contents, but high doses of Se had a negative impact on cowpea growth, regardless of P supply, resulting in reduced grain yield.
Keywords: Phosphate; Total sugars; Vigna unguiculata